High School Students' Motivation and Engagement in Online Learning - Tara, Lativa; Hidayati, Izzanil; Susanti, Meria (Utan Kayu Publishing, 2022)
This study aims to determine the effect of motivation toward student engagement of high school students in Padang city in online learning. The quantitative research method of simple linear regression analysis was used in this study. This study included 331 high school students who participated in online learning using random sampling techniques. The Motivated Strategies and Learning Questionnaire (MSLQ) and the Student Engagement Scale were applied to this study. Reliability on the motivation scale was .922 and the student engagement scale was .926. The results of this study indicate that motivation has a significant effect on student engagement in high school students in Padang City in online learning. This can be seen from the significance value of .000 (p less than .05) and the R-square coefficient (R2) value of .545. It can be concluded that motivation influences student engagement by 55%, while the remaining (45%) is influenced by other factors not investigated in this study.